Junk Food Consumption Behavior among Young Children - Banstola, Sanju; Shrestha, Nirmala; Sharma, Bimala (Journal of Nepal Health Research Council, 2024)
Background: Consumption of junk food degrades the health status of people and is associated with low consumption of nutritious foods, which are essential for physical and mental growth. This study was carried out to find out the junk food consumption and its associated factors among young children. Methods: A cross-sectional study was conducted among 352 school going children aged 5 to 9 years in Pokhara Metropolitan. Face to face interviews were done with one of the parents of the selected children with the help of a structured questionnaire. The study was done from March to October, 2020. Three or more consumption per week was categorized as high consumption of junk food. A descriptive and multivariate statistical analysis was performed. All inferential analyses were conducted at a 5% level of significance. Ethical approval was taken from the Nepal Health Research Council. Results: Among the study participants, 70.7% consumed junk food three or more times per week; 66.5% energy dense food, 20.7% consumed noodles; and 9.7% sugary drinks. Consumption of junk food was associated with presence of conventional shop near home,ways type of food provision at school and, food at home after school. Consumption of junk food was found higher among those who got money for food at school (AOR, 2.31), and those who took snacks at home after school (AOR, 12.86). Conclusions: Consumption of junk food among young children was remarkably high in the study area; concerned authorities should pay attention to dissociating such foods through policies and programs. Keywords: Children; junk food; Pokhara.